Attribution Retraining Group Counseling Technique to Reduce Student’s Learned Helplessness Behavior - Rachmawati, Ulvina; Purwanto, Edy; Awalya, Awalya (Jurnal Bimbingan Konseling, 2018)
This study aimed to determine the impact of attribution retraining group counseling technique on student’s learned helplessness. One-group pretest-posttest design was used in this study involving a total of 5 students as participants. The results of paired t-test showed that the student learned helplessness level can decreased at posttest (39.58%) than at assesment pre test (68.33%; t = 7.14, p < 0.01). Further, this study was focused to discuss the possibility of implementing attribution retraining in overcoming the problem of student’s learned helplessness behavior.